Locked up: a history of the US prison system - Edge, Laura B. (People's history, 2009)
Every crime a sin, every sin a crime -- Silent and separate -- The reform movement -- The progressive era -- The big house -- The corrections era -- A fight for rights -- Getting tough -- Now what?